Suicide in Young Age Group - Monsur, MA; Rahman, MM; Saha, KP; Haque, R; Mahmood, S (TAJ: Journal of Teachers Association, 2009)
This paper presents the study of 200 cases of death which were 'suicidal in nature' received in the dept. of Forensic Medicine, Sylhet MAG Osmani Medical College, Sylhet, Rajshahi Medical College, Rajshahi, Comilla Medical College, Comilla and Faridpur Medical College, Faridpur for Post Mortem examination (PME), during the period of 2007 to 2009, The post mortems were conducted by the authors. Out of 200 PME of Suicide cases 98 49%) were hanging by neck, 86 (43%) were poisoning and 16 (8%) by other methods. TAJ 2009; 22(1): 194-197